Weak dorsolateral prefrontal response to social criticism predicts worsened mood and symptoms following social conflict in people at familial risk for schizophrenia - Nook, Erik C. (Neuroimage Clin, 2018)
Understanding the specific mechanisms that explain why people who have relatives with schizophrenia (i.e., people at familial high risk; FHR) are more likely to develop the disorder is crucial for prevention. We investigated a diathesis-stress model of familial risk by testing whether FHR individuals under-recruit brain regions central to emotion regulation when exposed to social conflict, resulting in worse mood and symptoms following conflict. FHR and non-FHR participants listened to critical, neutral, and praising comments in an fMRI scanner before completing 4 weeks of daily-diary records. Compared to non-FHR individuals, FHR individuals under-recruited the bilateral dorsolateral prefrontal cortex (DLPFC)—a region strongly implicated in cognitive emotion regulation—following criticism. Furthermore, within FHR participants, weak DLPFC response to criticism in the laboratory task was associated with elevated negative mood and positive symptoms on days with distressing social conflicts in daily-diary assessments. Results extend diathesis-stress models of schizophrenia by clarifying neural and environmental pathways to dysregulation in FHR individuals.